A Pro-social Pill? The Potential of Pharmacological Treatments to Improve Social Outcomes After Pediatric Traumatic Brain Injury - Semple, Bridgette D.; Raghupathi, Ramesh (Frontiers in Neurology, 2021)
Traumatic brain injury (TBI) is a leading cause of injury-induced disability in young children worldwide, and social behavior impairments in this population are a significant challenge for affected patients and their families. The protracted trajectory of secondary injury processes triggered by a TBI during early life—alongside ongoing developmental maturation—offers an extended time window when therapeutic interventions may yield functional benefits. This mini-review explores the scarce but promising preclinical literature to date demonstrating that social behavior impairments after early life brain injuries can be modified by drug therapies. Compounds that provide broad neuroprotection, such as those targeting neuroinflammation, oxidative stress, axonal injury and/or myelination, may prevent social behavior impairments by reducing secondary neuropathology. Alternatively, targeted treatments that promote affiliative behaviors, exemplified by the neuropeptide oxytocin, may reduce the impact of social dysfunction after pediatric TBI. Complementary literature from other early life neurodevelopmental conditions such as hypoxic ischemic encephalopathy also provides avenues for future research in neurotrauma. Knowledge gaps in this emerging field are highlighted throughout, towards the goal of accelerating translational research to support optimal social functioning after a TBI during early childhood.